Development of tropical lowland peat forest phasic community zonations in the Kota Samarahan-Asajaya area, West Sarawak, Malaysia - Zulkifley, M.T.M.; Fatt, N.T.; Konjing, Z.; Ashraf, M.A. (Universidad Nacional de Colombia, 2016)
Logging observations of auger profiles (Tarmizi, 2014) indicate a vertical, downwards, general decrease of peat humification levels with depth in a tropical lowland peat forest in the Kota Samarahan-Asajaya área in the región of West Sarawak (Malaysia). Based on pollen analyses and field observations, the studied peat profiles can be interpreted as part of a progradation deltaic succession. Continued regression of sea levels, gave rise to the development of peat in a transitional mangrove to floodplain/floodbasin environment, followed by a shallow, topogenic peat depositional environment with riparian influence at approximately 2420 ± 30 years B.P. (until present time). The inferred peat vegetational succession reached Phasic Community I at approximately 2380 ± 30 years B.P. and followed by Phasic Community II at approximately 1780 ± 30 years B.P., towards the upper part of the present, ombrogenic, peat profile. Observations of the presence of large, hollow, Shorea type trees, supports that successive vegetational zonation of the tropical lowland peat dome may have reached Phasic Community II. Some pollen types were found that are also known to occur in the inferred vegetational zonation of Phasic Community III and IV or higher. Pollen analyses indicates that estuarine and deltaic, brackish to saline water influence may have gradually ceased at approximately 0.5 m below the lithological boundary between peat and underlying soil (floodplain deposit) in the tropical lowland peat basin.